MHC class II region, CTLA4 gene, and ophthalmopathy in patients with Graves' disease. - Allahabadia, A; Heward, J; Nithiyananthan, R; Gibson, S; Reuser, T; Dodson, P; Franklyn, J; Gough, S (2001)
Up to half of patients with Graves' hyperthyroidism have signs of thyroid associated ophthalmopathy, but the factors that cause this disorder are unknown. We investigated two major genetic susceptibility loci for Graves' disease in ophthalmopathy; the MHC class II region and the cytotoxic T lymphocyte antigen-4 (CTLA4) gene. Allelic frequencies of these genes in patients with Graves' disease who did and did not have concurrent thyroid-associated ophthalmopathy did not differ, and are, therefore, unlikely to contribute to its development.